The TNF Receptors p55 and p75 Mediate Chemotaxis of PMN Induced by TNFα and a TNFα 36–62 Peptide - Ø. Rekdal; Z. Konopski; J. S. Svendsen; J.-O. Winberg; T. Espevik; B. Østerud (Mediators of Inflammation)
The present study was performed to examine whether residues 36–62 of TNFα contain the chemotactic domain of TNFα, and whether the p55 and p75 TNF receptors are involved in TNFα induced chemotaxis. The chemotactic effect of TNFα on PMN was inhibited by the mAbs Hrt-7b and Utr-1, against the p55 and p75 TNF receptors, respectively. Both receptors may therefore be required for mediating the chemotactic effect of TNFcz. The synthetic TNFα 36–62, similar to TNFα, had chemotactic effects on both PMN and monocytes. The chemotactic activity of the TNFα 36–62 peptide on PMN, was inhibited by Htr-7b, Utr-1 and soluble p55 receptor, which shows that the peptide possessed the ability to induce chemotaxis through the TNF receptors. In contrast to TNFα, the peptide did not show a cytotoxic activity against WEHI 164 flbrosarcoma cells. It is suggested that different domains of the TNFα molecule induce distinct biological effects.